PENDAMPINGAN PENCATATAN TRANSAKSI KEUANGAN PADA KOPERASI MUSLIMAT NUR FATIMAH MALANG - Yuni Kusuma, Arumsari; Warter, Agustim (STIE PGRI Dewantara Jombang, 2025)
This Community Service Program (PKM) aimed to strengthen the managerial capacity of Koperasi Muslimat Nur Fatimah Malang through mentoring on financial transaction recording and financial statement preparation based on basic accounting principles. The cooperative’s main issues included unstructured manual bookkeeping and limited accounting knowledge among administrators. The three-month program used a participatory approach covering daily transaction recording, income statement and balance sheet preparation, cash flow analysis, and internal audit simulations. The results revealed significant improvement in the participants’ accounting skills and reporting accuracy. Pre- and post-test evaluations showed an increase in accounting comprehension from 52% to 87%. Additionally, the cooperative successfully established an internal finance team and implemented an Excel-based accounting system. This program enhanced transparency, accountability, and professionalism, enabling the women’s cooperative to adapt to modern financial management in the digital era.